AIR QUALITY IN SECONDARY SCHOOLS AND ITS IMPACT ON PUPILS' HEALTH AND WELL-BEING - Toshmatova G. A.; Niyazova O. A.; Erkinov I. A. (Journals Park Publishing, 2024)
This article examines the air quality in comprehensive schools and its impact on students’ health and learning. The study looked at the impact of air quality indicators such as carbon dioxide levels, dust particles, humidity, and chemicals. The results show that poor air quality negatively impacts students’ health and their ability to concentrate. Recommendations include improving ventilation, using air purifiers, and limiting the use of chemicals.
Keywords: Air quality, secondary schools, health, learning process, concentration, ventilation, dust particles, carbon dioxide.